Touch DNA: impact of handling time on touch deposit and evaluation of different recovery techniques: An experimental study - Sessa, Francesco (Sci Rep, 2019)
“Touch DNA” is DNA obtained from biological material transferred from a donor to an object or a person during physical contact. This particular kind of evidence could play an essential role in forensic laboratory work and is considered an important tool for investigators. Even though the principal aspects of “Touch DNA” have been extensively studied, to date, there are few reports in the research field of DNA retrieval from garments that have been worn. This study aimed to investigate the “handling time”, analyzing particularly the minimum contact time required to deposit a sufficient amount of DNA on a garment to produce an interpretable profile of the “handler”. Moreover, three different sampling techniques were compared (“dry swab”, “cutting out”, and “adhesive tape”) with the aim of defining the technique that guarantees the best recovery of the three methods tested. Analyzing the data of this experimental model, a “handling time” of two seconds is enough to release sufficient DNA on to a garment to obtain a complete profile. Moreover, this study demonstrated that when targeting for foreign DNA, the sample area should be narrowed down as much as possible to the smallest area possible to maximize target DNA recovery.